Fibrosarcoma of the ethmoid region - Seçil Bahar Akyol; N. Tan Ergin (Turkish Archives of Otorhinolaryngology, 2011)

(untitled)
In the treatment of head and neck malignancies, radiation therapy is an important adjunct. On the other hand exposure to the radiation is accepted as to induce sarcomas. Also tumors; appearing in the previously irradiated areas also have been reported. These tumors are with different histological features from the original tumors and named as irradiation induced tumours. Irradiation induced tumors following irradiation for head and neck cancers are quite rare, and very few of them are soft tissue sarcomas. We report a very rare case of fibrosarcoma of the head and neck following radiation therapy for orbital rhabdomyosarcoma.